Cana-de-açúcar em bacias hidrográficas experimentais irrigadas - Silva, Vanessa Lorencini da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Understanding the spatial distribution of crops, based on topographic information, can provide opportunities for specific management applications. With this work is aimed to quantify the effect of the exposure, slope and irrigation influence on the production of second cut of sugar cane. The research was developed in the experimental area of the Department of Agricultural Engineering of FCAV / UNESP, called Experimental Hydrographic Basins with areas of 10.5 m², two in the horizontal and the other with a gradient of 10, 20, 30, 40 and 50% and exhibitions north, south, east and west. Drip irrigation was performed on all surfaces, except in a horizontal. The variety used was the RB855453. At harvest were analyzed the masses of the stems, number of tillers, productivity, total recoverable sugar (ATR in Portuguese) and fiber. The production of sugar cane was affected by exposure, being favored in western exposure. The greatest yields occurred in W10, W20 and W40 surfaces

Compreender a distribuição espacial das culturas, baseada em informações topográficas, pode fornecer oportunidades de aplicações específicas de manejo. Com esse trabalho objetivou-se quantificar o efeito da influência da exposição, declividade e da irrigação sobre a produção do segundo corte da cana-de-açúcar. A pesquisa foi desenvolvida na área experimental do Departamento de Engenharia Rural da FCAV/UNESP, denominada Bacias Hidrográficas Experimentais com superfícies de 10,5 m², duas na horizontal e as demais com declividade de 10, 20, 30, 40 e 50 % e exposições norte, sul, leste e oeste. A irrigação por gotejamento foi realizada em todas as superfícies, exceto em uma horizontal. A variedade utilizada foi a RB855453. No momento da colheita foram analisadas as massas dos colmos, número de perfilhos, produtividade, ATR e Fibra. A produção de cana-de-açúcar foi influenciada significativamente pela exposição, sendo favorecida na exposição oeste. Os maiores valores de produtividade ocorreram nas superfícies W10, W20 e W40
Keywords: Cana-de-açúcar; Irrigação agricola; Radiação solar; Superficie; Produtividade agrícola